Improving teaching in different disciplines of natural science and mathematics with innovative technologies - Kossybayeva, U.; Shaldykova, B.; Akhmanova, D.; Kulanina, S. (Education and Information Technologies, 2022)
The study describes an innovative methodology for teaching natural and mathematical sciences in the context of distance learning using modern technological solutions and based on the concepts of active social learning that involves constructivist, problem-oriented, project and research approaches. The proposed methodology was tested on 80 students enrolled in two training courses in [BLINDED] University and [BLINDED] University, respectively: Mathematics Teaching in the Content and Language Integrated Learning (CLIL) context and Molecular Biology. The psychological safety of the proposed pedagogical methodology was investigated by assessing the level of psychological well-being of the participants in the educational process using the Scale of psychological well-being questionnaire developed by C. D. Ryff that was adapted to the educational context. The results of the study showed that the proposed pedagogical methodology was safe in relation to the life of students. It generally improved their perception of learning and themselves in the role of its participants, promoted positive self-esteem in group learning contacts, and, by developing learning involvement and interest through the Clil technology, qualitatively contributed to the achievement of educational progress by each student. The developed innovative methodology for teaching natural and mathematical sciences can be used as a pedagogical model for developing effective training courses. The demonstrated assessment of the level of psychological well-being adapted to the educational context can serve as a basis for the development of motivational learning strategies that support students in crisis learning conditions during the pandemic.
Keywords: Clil technology; Distance learning; Innovative teaching methods; Motivational learning strategy; Natural and mathematical sciences; Psychological well-being